Manajemen Pengembangan Profesionalisme Guru Pendidikan Agama Islam di Sekolah Menengah (JMPI: Jurnal Manajemen Pendidikan Islam, 2026)
This study examines the management of professional development of Islamic Religious Education (PAI) teachers in secondary schools, focusing on planning, implementation, evaluation, and follow-up processes. The research employs a qualitative approach with a literature study method, drawing on relevant books, journal articles, and prior studies published within the last decade. Data were collected through documentation techniques and analyzed using content analysis to identify patterns and relationships among concepts. The findings indicate that the planning of professional development programs has not been fully based on comprehensive needs assessments and lacks active teacher participation. The implementation stage involves both formal and informal activities; however, it is constrained by limited time, insufficient relevance of training materials, and lack of program continuity. Furthermore, evaluation practices tend to be administrative rather than analytical, resulting in weak follow-up actions. The study also reveals that teacher motivation, school leadership support, and a conducive working environment serve as key supporting factors, while limited resources, unequal access to training, and resistance to change act as significant barriers. Overall, effective management of teacher professional development requires a systematic, participatory, and sustainable approach to enhance teacher competence and improve the quality of learning. Keywords: professional development management, Islamic Religious Education teachers, secondary education, teacher competence, educational quality